Behaviour of the order parameter of the simple magnet in an external field - Kozlovskii, M.P.; Pylyuk, I.V.; Prytula, O.O. (Condensed Matter Physics, 2005)
The effect of a homogeneous external field on the three-dimensional uniaxial
magnet behaviour near the critical point is investigated within the framework
of the nonperturbative collective variables method using the ρ⁴ model.
The research is carried out for the low-temperature region. The analytic
explicit expressions for the free energy, average spin moment and susceptibility
are obtained for weak and strong fields in comparison with the field
value belonging to the pseudocritical line. The calculations are performed
on the microscopic level without any adjusting parameters. It is established
that the long-wave fluctuations of the order parameter play a crucial role
in forming a crossover between the temperature-dependence and fielddependence
critical behaviour of the system. В рамках непертурбативного методу колективних змінних на основі
моделі ρ⁴ досліджено вплив зовнішнього поля на критичну поведінку тривимірного одновісного магнетика. Дослідження проведені
для низькотемпературної області. Отримані аналітичні вирази для
вільної енергії, середнього спінового моменту і сприйнятливості
у випадку слабких і сильних полів по відношенню до величини
поля, що задовільняє рівняння псевдокритичної лінії. Розрахунки
проведені на мікроскопічному рівні без застосування допоміжних
параметрів. Встановлено, що вирішальну роль у формуванні переходу між температурозалежною і залежною від поля критичною
поведінкою системи відіграють довгохвильові флуктуації параметра
порядку.